THE SUSTAINABLE CONCEPT DESIGN CONCERNING THE IMPLEMENTATION OF LOW IMPACT DEVELOPMENT IN URBAN AREA (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2025)
The relationship between water quantity and water quality status in the framework of water resources management was complex and likely to be site-specific, thus the cause-effect relationships between pollutant sources (affluents) and water quality condition remain unclear. The primary principle of Low Impact Development (LID) concept design is to detain and/or hold stormwater for as long as possible and to limit stormwater pollution before it enters major waterbodies. LID methods aim to preserve as much water on-site as feasible while also protecting water quality through the use of natural landscape elements. We also highlighted the results of preliminary data to design for the implementation of LID. The water quantity and water quality status relationship in the framework of water resources management was complex and likely to be site-specific, therefore the cause-effect relationships between pollutant sources (affluents) and water quality condition still need to be clearly quantified. The core concept of Low Impact Development (LID) is to detain and/or retain stormwater as long as possible and to reduce the stormwater runoff pollutions before flowing into main waterbodies. LID components seek to keep water onsite as much as possible and protect water quality using landscape natural features. Therefore, the main objective of this paper was to offer the opportunities of applying LID components in urban area. We also summarized the performances of LID components including the improvement of water quality from previous studies.